A STUDY OF RELATIONSHIP OF ABO BLOOD GROUPS WITH MYOCARDIAL INFARCTION AND ANGINA PECTORIS - AKHUND, ISRAR AHMED; ALVI, IRSHAD ALI; ANSARI, ASMAT KAMAL; Mughal, Muhammad Azhar; Akhund, Anwar Ali (Journal of Ayub Medical College Abbottabad, 2001)
Background: This is a comprehensive report that has determined the occurrence of Myocardial infarction and Angina pectoris in "ABO" blood group system among patients with coronary artery disease in some areas of Sindh province of Pakistan. Methods: Three hundred patients with Coronary Disease (CAD) were selected from cardiology wards of LMC hospital Hyderabad, DMC hospital Karachi and PMC hospital Nawabshah. The patients were separated into two categories: myocardial infarction and angina pectoris. The patients with old myocardial infarction were also included. A careful history was taken, suggesting myocardial infarction (MI) or angina from a standard WHO (Rose) chest pain, and an electrocardiogram showing evidence of possible myocardial infarction and angina, and the patient's recall of a doctor's diagnosis of M.I or angina. ABO blood grouping of above patients was done by simple agglutination method. Results: The blood group "A" was the commonest among myocardial infarction and angina pectoris patients while these diseases were least in blood group "O" patients. Conclusions: This comparison shows the existence of a direct relation between blood group antigens and coronary artery disease. It is therefore of great importance for future genetic studies, as present report and our previous studies give clear picture of excess and deficit of CAD in particular blood groups of "ABO" system. This may be due to some special genetic makeup